Data Voids: Where Missing Data Can Easily Be Exploited - Golebiewski, Michael; boyd, danah (Data & Society, 2019)
Data Voids demonstrates how manipulators expose people to problematic content by exploiting search engine results. “Data voids are a security vulnerability that must be systematically, intentionally, and thoughtfully managed.” Michael Golebiewski of Microsoft coined the term “data void” in May 2018 to describe search engine queries that turn up little to no results, especially when the query is rather obscure, or not searched often. In Data Voids: Where Missing Data Can Easily Be Exploited, Golebiewski teams up with danah boyd (Microsoft Research; Data & Society) to demonstrate how data voids are exploited by manipulators eager to expose people to problematic content including falsehoods, misinformation, and disinformation.